Aspectos de la biología y el consumo de Neoseiulus cucumeris y Typhlodromalus aripo (Acari: Phytoseiidae) con la presa Thrips palmi (Thysanoptera: Thripidae) - Cuéllar Jimenez, M.E.; Bellotti, Anthony C.; Melo Molina, E.L. (2002)
Thrips palmi Karny is an important pest of several crops, especially vegetables. The predatory mite Neoseiulus cucumeris has been successfully used in the control of various thrips species. The predatory mite T. aripo also has shown considerable capacity to consume cassava thrips. The potential impact of N. cucumeris and T. aripo on populations of T. palmi was evaluated. The objectives were, to determine the effects of consumption of T. palmi on the biology of N. cucumeris and T. aripo, and to compare to mite prey species Tetranychus urticae and Mononychellus caribbeanae; to quantify the consumption of the predators on T. palmi and evaluate the functional response of N. cucumeris and T. aripo to densities of 1, 3, 5, 10, 20 y 4O of first instar larvae of T. palmi. The studies were carried out under laboratory conditions (25 ± 5°C, 75 ± 5% of r. h. and 12:12 L:D). The development period of N. cucumeris when feeding on T. palmi and T. urticae was 8.9 and 8.5 days respectively. For T. aripo it was 15.1 days with T. palmi and 13.5 days with M. caribbeanae. Fecundity for N. cucumeris and T. aripo was 25.2 and 15.6 respectively, being higher on T. palmi than mite prey. The percentage of females in the population and longevity of predatory mites were similar with both prey species offered. N. cucumeris was the predator with the higher fecundity and longevity. An individual of N. cucumeris consumed 65.3 first instar larvae of T. palmi and 18.7 second instar larvae during its life cycle. T. aripo consumed 72.9 first instar larvae of T. palmi and 21.6 second instar larvae during its life cycle. N. cucumeris and T. aripo females displayed a type II functional response, consuming 16 and 18 first instar T. palmi in 24 hours, responding positively to higher densities of thrips.